The Gospel of Matthew : Walter T. Wilson. - Wilson, Walter T. (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2022)
"The first volume of a magisterial commentary for scholars, students, pastors, and interested laypersons that interprets the Gospel of Matthew in its first-century context; and The second volume of a magisterial commentary for scholars, students, pastors, and interested laypersons that interprets the Gospel of Matthew in its first-century context"--
volume 1. Matthew 1-13 -- volume 2. Matthew 14-28.
Includes bibliographical references and indexes.
Keywords: Bible. -- Commentaries